Propreté et malpropreté des espaces privés et publics urbains au Liban - Nada Chbat (Projets de Paysage)
In Lebanon, the problem of hygiene does not arise at the private property level because every inhabitant, according to agreed social rules, takes naturally the adequate measures in order to assure the cleanliness of his/her house. The question of the cleanliness is distinctly more complex. Everyone believes indeed that he has a right to the permanent quality of his life frame. Everyone tends to reject the responsibility of the public space cleanliness on the others. This is also the consequence of the public space statute as a residual space of the private constructions. However, the public powers don’t guarantee everywhere the service of cleanliness, out of the domicile, except if this service is bought (on the private beaches for example).